Modeling of Processes on Timely Control of Operational Medium Supply and Distribution Regime in Hydraulic Network Systems - M. Ya. Panov; V. I. Shcherbakov; G. N. Martinenko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper proposes a model of disturbed state in the area of backward analysis. This model permits to formalize synthesis of throttle characteristics of the system. It provides the possibility to forecast consumption of operational medium within the scope of timely system control.